Integration of biological control with engineered heterojunction nano-photocatalysts for sustainable and effective management of water hyacinth weed. Issue 1 (February 2022) - Jawed, Aquib; Kar, Prasenjit; Verma, Rahul; Shukla, Komal; Hemanth, P.; Thakur, Vijay Kumar; Pandey, Lalit M.; Gupta, Raju Kumar
Abstract: Water hyacinth ( Eichhornia crassipes ) is a noxious weed that has gained global attention because of its rapid spread and congested development, causing allergies in navigation, irrigation, and challenges navigation, irrigation, and aquatic life challenges. Different physical, chemical, and biological methods are being used to control water hyacinth. However, cost, duration, toxicity, resurgence, and water pollution remain a bottleneck. Integrated controls are reported to be the most cost-effective choice. The generation of reactive oxygen species (ROS) by chemical herbicides is the primary mechanism of action, which damages cell membranes leading to the inactivation of water hyacinth. The engineered heterojunction photocatalysts efficiently generate ROS under visible light and can be applied as alternatives to herbicides. In addition, these photocatalysts offer the advantage of the simultaneous remediation of wastewater as well. This report examines current research activity in the subject, focusing on the scientific and technological opportunities by visible light photocatalysts (VLP). The preparation of floating photocatalysts via composite granules or porous structures has been highlighted to be utilized to control aquatic weeds. The mechanisms of photocatalytic activity of VLP and inactivation of water hyacinth have been discussed. The integrated photocatalytic and biological controls are proposed for the sustainable and effective management of water hyacinth. Graphical Abstract: ga1 Highlights: Water hyacinth (Eichhornia crassipes) is a noxious weed that has gained global. Different physical, chemical, and biological methods being used to control water hyacinth. The generation of ROS by chemical herbicides is the primary mechanism leading to the inactivation of water hyacinth. Examines current research activity in the subject, focusing on scientific and technological opportunities by VLP. The mechanisms of photocatalytic activity of VLP and inactivation of water hyacinth have been discussed.